(untitled) (Innovative professional education, 2024)
The algorithm and expediency of introducing eco-oriented pedagogical technologies into professional training of future qualified workers in the construction, agrarian and restaurant industries are analyzed in the context of scientific research of the laboratory of vocational training technologies.